Effect of β recrystallization on the precipitation evolution of primary α phase and the phase transformation inheritance during thermomechanical processing in Ti-55511 alloy - Yue Dong; Xingang Liu; Haozhe Niu; Hao Xu; Yini He; Yujiao Ke; Wenwen Zhang (Journal of Materials Research and Technology, 2023)
The crystallographic defects introduced after thermal deformation of near-β Ti-55511 alloy can have an important impact on the precipitation of primary α phase (αp), β grain evolution and the texture evolution during the subsequent heat treatment. The investigation indicates that the intragranular short-rod αp precipitated by strain-induced nucleation deviates from Burgers orientation relationship (BOR) by boundary splitting in 0.27–0.64, accompanied by β→αp transformation, which strictly obeys BOR during ST. In addition, the strain and strain rate can modify the αp-type after deformation. Three main αp types are Type I: 50–60°/<-12-10>, Type II: 40–50° or 80–90°/<01–10> and Type III: 90–100°/<-27-53>. The phase transformation inheritance occurs after ST based on the variant selection effect, and the αp varieties are mainly 80–90°/<-12-10> and 80–90°/<01–10>. Furthermore, the density of the deformation texture (000–1) [11–20] is weakened by the new αp transformation texture (0001) [-1-780] and the recrystallization texture (23-5-3) [11–22], but it is inherited at 1.23. However, the αp recrystallization texture significantly restrains the occurrence of the deformation texture inheritance phenomenon at 0.001 s−1. Moreover, the adjacent αp grains are mainly 60°/<11–20> to each other, while the β grains around αp with a relatively high degree of recrystallization are mainly 30–50°/<34x> to each other. The first one of the static sphericalized αp is partly generated by coarsening, which is derived from the dispersed nucleus αp precipitated at the trigonal/tetragonal β sub-boundaries. The second one is by the GB separation mechanism triggered by the formation of α/α boundaries within the short-bar αp grain.